Sufferings, Resilience, and Triumph over Despair in Linda Sue Park’s A Long Walk to Water - Shrestha, Kumar (Bon Voyage, 2024)
This research paper explores the plights of the refugees and their experiences in the place of origin, during the journey and in the host country, which are similar and caused by the same entity of state sovereignty and the use of state of exception in the text A Long Walk to Water. The civil war in Sudan compels Salva and many Sudanese people to leave their home country and live the very painful lives. Their plight is generally universal plight of every asylum seeker. In A Long Walk to Water, Salva starts facing a new set of obstacles after leaving his home country, Sudan and continues even in the host country. Despite the daunting obstacles, Salva's extraordinary resilience, determination, and willingness to adapt enables him to overcome his sufferings. This research paper finally argues that the problems of the right less/stateless people will have to be addressed by creating an unshakable framework by combining ideas of universal right to the political space with ethics of unconditional hospitality. Towards a creating an equal space for every individual, Hannah Ardent’s rights to have right, Kant’s universal hospitality and Derrida’s unconditional hospitality can be instrumental to minimize the sufferings of the refugees in this world. To improve and alleviate the sufferings of refugees, their rights will have to come from their equal access to the political space and legalization of their rights will have to be guided by humanitarian perspectives.